Enhancing Creative Arabic Writing Competence Through Project-Based Learning - Dadan Nugraha; Vina Fatimatu Zahra; Shaker Abd Al-Manan; Nadatul Paujiyah (UIN Sunan Gunung Djati Bandung, 2025)
This research investigates the effectiveness of a Project-Based Learning (PBL) model in enhancing Arabic creative writing skills among eighth-grade students at MTs Al-Mukhtariyah Tasikmalaya. Employing a classroom action research design conducted in two cycles, the research integrated systematic planning, implementation, observation, and reflection stages. Students’ creative writing performance was assessed using an analytic writing rubric covering idea development, linguistic accuracy, creativity, and text organization. The findings reveal a notable improvement in students’ writing competence, as indicated by an increase in the mean score from 59.28 in the first cycle to 70 in the second cycle, accompanied by a rise in learning mastery from 52.38% to 71.43%. Beyond quantitative gains, the PBL model fostered higher learner engagement, collaboration, and creative expression in Arabic writing tasks. This research contributes to Arabic language pedagogy by providing empirical evidence on the pedagogical value of PBL at the lower secondary level and highlights its potential as an instructional alternative for developing creative writing skills. Practically, the findings underscore the importance of teacher-designed project activities in facilitating meaningful and student-centered Arabic writing instruction.